Violence in European medieval monasteries: Skeletal trauma in Teplá monastery (Czech Republic). (23rd July 2019) - Pankowská, Anna; Galeta, Patrik; Uhlík Spěváčková, Petra; Nováček, Karel
Abstract: Medieval monasteries often went beyond their religious mission and developed into economic, social, and educational centres. These were not spared from violent attack on the part of the gentry. The defence of such monasteries is, however, a poorly investigated area in bioarchaeological studies. A recently excavated skeletal sample found in front of the western gate of the Abbey Church at the Teplá monastery (Czech Republic) dated between the 13th and 15th century AD provides us a unique opportunity to fill this gap. The analysis of skeletal trauma reveals that 13 out of 30 individuals exhibited trauma, of which 69% were confidently related to violence. All individuals with injuries were males, and half of them were younger than 30 years of age. The presence of ante‐mortem injuries indicates that males likely had previous combat experience, were successfully treated, and their bodies were buried with respect and care. The most probable explanation of our findings is that the individuals were a group of clients who were tasked with the defence of the Teplá monastery. Other, less likely explanations assume that individuals were laity, monastery benefactors, and/or canons killed during several different violent attacks directed at the monastery.